A rare case of perforating intrauterine contraceptive device - Singh, Sarita; ., Saima; ., Jagriti; Dewan, Rupali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The trends in the acceptability of contraceptives is globally shifting from permanent sterilisation to long acting reversible contraceptive (LARC). With the increasing use of IUCD, the knowledge of its common and rare complications has become pertinent. One of them is cervical perforation in which strings are mostly visible and hence it can be easily missed. Here we present a rare case of cervical perforation which was timely detected before it could have caused more damage. A patient complaining of IUCD associated pain should undergo thorough examination and a probability of perforation should be kept in differential diagnosis despite string visibility. A clinician has to be more vigilant about this rare complication to prevent damage to cervix and avoid unwanted pregnancy.